Variations de la croissance radiale de Quercus ilex L en fonction du climat - Zhang, S H; Romane, F (Ann. For. Sci., 1991)
Diameter growth of Quercus ilex L and the interannual variability of climatic characteristics. Diameter growth of Quercus ilex L, the dominant sclerophyllous species in much of the Mediterranean basin vegetation, was studied in relation to precipitation and temperature. The study site in Montpellier (Southern France) has a Mediterranean climate. Eleven trees, grown from acorns in 1963, were cut in 1984 and the rings studied at 3 levels (ground, 0.5 and 1 m above the ground). The data were analyzed by the ARMA procedure which gives the part of the total variation due to the autocorrelation processes. A multiple regression between the factors of a principal component analysis (PCA) of the monthly climatic data (rainfall and temperature) and the residuals issuing from the ARMA procedure then suggested that the large annual rings were due to a particular rainfall distribution during the year, the late summer precipitation promoting a large annual growth diameter (table II). The presence or absence of false rings (table I) was also analyzed by PCA (figs 2 and 3). The false rings were positively correlated to a large annual growth diameter corresponding to a high summer rainfall (fig 4), while the relationship with the temperature preceding the growing season was negative. It therefore appears that this species is relatively unaffected by spring climatic conditions, ie which generally indicate the main growth phase, but that it is able to take advantage of the interannual climatic variations of the region.
Keywords: diameter growth; Mediterranean climate; Precipitation; Quercus ilex L; ring; Temperature